Effect of different intensities of physical activity on cardiometabolic markers and vascular and cardiac function in adult rats fed with a high-fat high-carbohydrate diet - Romeo B. Batacan, Jr; Mitch J. Duncan; Vincent J. Dalbo; Geraldine L. Buitrago; Andrew S. Fenning (Elsevier, 2018)
Background: Physical activity (PA) and diet are 2 lifestyle factors that affect cardiometabolic risk. However, data on how a high-fat high-carbohydrate (HFHC) diet influences the effect of different intensities of PA on cardiometabolic health and cardiovascular function in a controlled setting are yet to be fully established. This study investigated the effect of sedentary behavior, light-intensity training (LIT), and high-intensity interval training (HIIT) on cardiometabolic markers and vascular and cardiac function in HFHC-fed adult rats. Methods: Twelve-week-old Wistar rats were randomly allocated to 4 groups (12 rats/group): control (CTL), sedentary (SED), LIT, and HIIT. Biometric indices, glucose and lipid control, inflammatory and oxidative stress markers, vascular reactivity, and cardiac electrophysiology of the experimental groups were examined after 12 weeks of HFHC-diet feeding and PA interventions. Results: The SED group had slower cardiac conduction (p = 0.0426) and greater thoracic aortic contractile responses (p < 0.05) compared with the CTL group. The LIT group showed improved cardiac conduction compared with the SED group (p = 0.0003), and the HIIT group showed decreased mesenteric artery contractile responses compared with all other groups and improved endothelium-dependent mesenteric artery relaxation compared with the LIT group (both p < 0.05). The LIT and HIIT groups had lower visceral (p = 0.0057 for LIT, p = 0.0120 for HIIT) and epididymal fat (p < 0.0001 for LIT, p = 0.0002 for HIIT) compared with the CTL group. Conclusion: LIT induced positive adaptations on fat accumulation and cardiac conduction, and HIIT induced a positive effect on fat accumulation, mesenteric artery contraction, and endothelium-dependent relaxation. No other differences were observed between groups. These findings suggest that few positive health effects can be achieved through LIT and HIIT when consuming a chronic and sustained HFHC diet.